Adult‐onset type 1 diabetic patients with less severe clinical manifestation have less risk DR‐DQ genotypes than childhood‐onset patients. Issue 1 (21st June 2020) - Ren, Wenqian; Yang, Daizhi; Jiang, Ziyu; Xian, Yingxin; Huang, Qianwen; Luo, Sihui; Zheng, Xueying; Yan, Jinhua; Xu, Wen; Yao, Bin; Wang, Cong‐Yi; Bei, Jin‐Xin; et al.
Abstract: Background: The aim of this study was to investigate differences in clinical features and HLA genotypes between adult‐onset and childhood‐onset patients with type 1 diabetes in a Chinese population. Materials and Methods: This study enrolled 716 Han Chinese patients with type 1 diabetes from Guangdong (258 childhood‐onset and 458 adult‐onset) to compare their clinical features. Of them 214 patients with classical type 1 diabetes (100 childhood‐onset and 114 adult‐onset) were selected for HLA DR and DQ genotyping by next‐generation sequencing. Results: Adult‐onset patients were characterized by longer duration of symptoms before diagnosis, lower frequency of DKA at disease onset, less frequent autoantibody positivity, higher serum C‐peptide concentrations, and better glycemic control. These findings were replicated in the restricted cohort of 214 patients with classical type 1 diabetes . Compared with childhood‐onset patients, adult‐onset patients had a lower frequency of the DR9 haplotype, as well as lower frequency of high‐risk DR3/DR4 and DR3/DR9 genotypes, but higher frequency of DR3 / DR3 genotype and DR3 /X, DR4 /X or DR9 /X (X, non‐risk) genotypes. Conclusions: Adult‐onset type 1 diabetic patients with susceptible haplotypes ( DR3, DR4 or DR9 ) were more likely to carry protective DR‐DQ haplotypes than childhood‐onset patients, which suggested the association between less risk DR‐DQ genotypes and the less severe clinical manifestation in adult‐onset patients.